Expertise Rents from Insider Trading for Financial Experts on Audit Committees - Duellman, Scott; Guo, Jun; Zhang, Yan; Zhou, Nan (Contemporary Accounting Research, 2018)
Abstract We document the existence of expertise rents by finding that financial experts on audit committees obtain higher abnormal returns from insider purchases than do non‐financial experts on audit committees. We further investigate whether information processing skills work alone or jointly with an information advantage to generate expertise rents. While financial experts on audit committees outperform financial experts on other committees, financial experts on compensation, executive, nominating, and governance committees do not outperform non‐financial experts on these committees. These findings suggest that expertise rents are domain‐specific and can be obtained only when directors have both access to private information and information processing skills. In additional testing, we find that expertise rents for financial experts on audit committees are primarily driven by non‐accounting financial experts, whose finance or supervisory experience could make them better than accounting financial experts in understanding market conditions and assessing firm risk.